1996
DOI: 10.1017/s0950268800059203
|View full text |Cite
|
Sign up to set email alerts
|

A study of maternally derived measles antibody in infants born to naturally infected and vaccinated women

Abstract: SUMMARYMaternal, cord and infant measles antibody levels were measured and compared in a group of 411 vaccinated mothers and 240 unvaccinated mothers, and their babies, between 1983 and 1991. Maternal and cord sera were tested by haemagglutination inhibition and/or enzymelinked immunosorbent assay, and plaque reduction neutralization tests were also used to test infant sera. Geometric mean titres were significantly higher in the unvaccinated than in the vaccinated mothers (P < 0-001). Infants born to mothers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 24 publications
3
40
0
Order By: Relevance
“…Several studies have shown that newborns from vaccinated mothers have both lower levels of transplacentally transferred measles antibodies than infants born from women who had measles and an earlier decline in maternal antibodies (1,4,12,15,30,37,38,40). In this study, the measles antibody levels determined for infants at 0 to 3 months of age were higher in infants born from mothers who had had natural measles infections than in infants of vaccinated mothers.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Several studies have shown that newborns from vaccinated mothers have both lower levels of transplacentally transferred measles antibodies than infants born from women who had measles and an earlier decline in maternal antibodies (1,4,12,15,30,37,38,40). In this study, the measles antibody levels determined for infants at 0 to 3 months of age were higher in infants born from mothers who had had natural measles infections than in infants of vaccinated mothers.…”
Section: Discussionmentioning
confidence: 50%
“…Measles vaccine coverage of infants (with a single dose at 24 months of age) increased from 19% in 1979 to 35% in 1983, 57% in 1987, and 80% in 1994 and then remained relatively unchanged until 2004, when it reached 87% (4,10).…”
mentioning
confidence: 99%
“…(19,34,35) .This low observed occurrence in children of vaccination and mothers with a past history of measles be able to explained through the information that these mothers have naturally acquired protection against measles, which provides passive defense to their infants (36) .The attendance of IgM antibodies to MV in serum is analytic of innate measles disease or vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Sethi et al found that IgG levels of low-birth-weight newborns (weighing less than 2 standard deviations below the expected weight for gestational age due to maternal illness during pregnancy) were lower than the antibody levels of normal weight infants of healthy mothers [25]. It is obvious that the decrease in serum IgG levels in infants born to mothers with antenatal illness is mainly due to the effects of maternal malnutrition and may possibly be related to the placental pathology commonly observed in these pregnancies [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although our study did not include measuring maternal antibodies to the 3 diseases in the mothers of the studied infants, it is assumed to be highest among mothers with a history of infection. A study conducted in both developing and developed countries that measured maternal-specific antibodies to measles found that mothers who contracted measles had significantly higher levels of antibodies and higher seroprevalence rates among their infants than mothers who were vaccinated [26]. It has been suggested that the children of women who have received measles vaccine might be successfully immunized at an earlier age than the children of women who have had measles [14].…”
Section: Discussionmentioning
confidence: 99%